THE VIEW OF FOREIGN ANALYSTS ON THE REFORM OF THE SOVIET PLANNING SYSTEM OF THE 80S OF THE XX CENTURY - M. B. Nazarenko (Вестник университета)
The article сonsiders the assessments of attempts to improve the economic mechanism of the USSR in the late 1970s - first half of the 1980s, which are contained in the works of foreign analysts. The paper pays particular attention to their analysis of the effectiveness of the reform of the economic mechanism in 1979, as well as the brigade and collective contracts introduced in the USSR in the early 1980s, and the economic experiment of 1984. The author gives both positive and negative assessments of these transformations in the Soviet economy, notes their strengths and weaknesses. The paper shows that the estimates and data contained in foreign studies allow us correlate the modern interpretation of the economic system in the USSR of the late socialist period.